Development of a Web-Based Information System for Post-Disaster Sanitation Management and Clean Water Distribution - Gunawan, Chicha Rizka; Gunawan, Chichi Rizka; Fadhilla, Cut Alna; Z, Muhammad Daffa (Lembaga Riset dan Inovasi Al-Matani, 2026)
Post-disaster conditions often cause disruption to sanitation systems and clean water distribution, which can increase the risk of environmental-based diseases and reduce the quality of life of affected communities. In many cases, the management of sanitation and clean water distribution is still carried out manually, leading to inefficiencies, data inaccuracies, and lack of coordination. This community service activity aims to develop and implement a web-based information system to support sanitation management and clean water distribution in post-disaster areas. The method used includes system development using a prototype approach, training for village officials and volunteers, and evaluation based on distribution efficiency, data accuracy, and user satisfaction. The results show that the system improves the efficiency of clean water distribution, enhances data accuracy, and facilitates real-time monitoring of sanitation conditions. The main contribution of this activity is the provision of a digital-based model for sanitation and water management that is applicable at the village level to support effective, transparent, and sustainable disaster management. However, limitations include dependence on internet infrastructure and user readiness.